Pengaruh Strategi Pemasaran terhadap Meningkatkan Volume Penjualan Usaha Pabrik Roti Bhaiya Kelurahan Pasar Hilir - Muhammad Husein; Muhammad Ardiansyah; Arwin Arwin (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
"The Influence of Marketing Strategy on Increasing the Sales Volume of the Bhaiya Bread Factory Business, Pasar Hilir Village, Panyabungan District, Mandailing Natal Regency" aims to find out the extent to which marketing strategies affect the increase in sales volume. The company was established to obtain maximum profit, so marketing effectiveness is an important component in attracting consumers and expanding market share. A good marketing strategy allows companies to build long-term relationships with customers, increase competitive advantages, and maintain business existence in the midst of increasingly fierce competition. In addition, implementing the right marketing strategy also helps companies understand consumer needs, position products more effectively, and adjust the marketing mix according to market dynamics. This study used a quantitative approach with the Accidental Sampling method on 96 respondents and simple linear regression analysis to test the influence of variables. The results of the study showed that marketing strategy had a positive and significant effect on sales volume with a significance value of 0.000 < 0.05. The value of the determination coefficient (R²) is 0.220, which means that 22% of the change in sales volume is explained by marketing strategy, while the remaining 78% is influenced by other factors such as product quality, price, location, consumer preferences, and the intensity of promotions carried out by competitors in the region.